Improving Reading Ability of Q.S. An-Nasr with Demonstration Method and Problem Based Learning Model in Elementary School Students - Nurlaili; Khairani, Laila; Nurlatifah (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' reading ability in the letter An-Nasr by using the demonstration method and problem-based learning model. This study uses a type of classroom action research. The design of this study uses the Kemmis & Mctaggart design with four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. Data were obtained using test and observation techniques. The data obtained were then analyzed using descriptive statistical techniques. The results of the study indicate that the demonstration method and problem-based learning model can improve students' reading ability in the letter An-Nasr in Islamic religious education learning. This can be seen in cycle I with an average percentage of 50% and in cycle II of 86%. So it can be stated that students' reading ability developed in cycle II. Improving students' reading ability through the application of the demonstration method and problem-based learning model on the material of the letter An-Nasr was carried out for two cycles. Learning outcomes in cycle I were 66.67% and in cycle II of 76.67%. So it can be stated that students' reading ability improved better in cycle II. Based on this, the demonstration method and problem-based learning model can be used as one of the media that can be considered by teachers to overcome the problem of low ability to read the Al-Quran in Islamic religious education learning.